2013
DOI: 10.1371/journal.pone.0074325
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Suppressors of Drosophila Kinesin Deficiency Rescue Motor Axon Development in a Zebrafish Model of Spinal Muscular Atrophy

Abstract: Proximal spinal muscular atrophy (SMA) is the most common inherited motor neuropathy and the leading hereditary cause of infant mortality. Currently there is no effective treatment for the disease, reflecting a need for pharmacologic interventions that restore performance of dysfunctional motor neurons or suppress the consequences of their dysfunction. In a series of assays relevant to motor neuron biology, we explored the activities of a collection of tetrahydroindoles that were reported to alter the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…Pharmacological or genetic suppression of ubiquitin-like modifier activating enzyme 1 (UBA1) was sufficient to recapitulate an SMA-like neuromuscular pathology in zebrafish, suggesting that UBA1 directly has an important role in disease pathogenesis. Tetrahydroindoles that alter the processing of amyloid precursor protein were tested in these various models and revealed that three of these compounds rescued motor neuron defects in smn morpholino knockdown zebrafish ( Gassman et al, 2013 ). More generally, the results suggest that SMA could be an axonopathy (a disease in which the normal function of axons is disrupted), suggesting novel strategies for treating the disease.…”
Section: Spinal Muscular Atrophy (Sma)mentioning
confidence: 99%
“…Pharmacological or genetic suppression of ubiquitin-like modifier activating enzyme 1 (UBA1) was sufficient to recapitulate an SMA-like neuromuscular pathology in zebrafish, suggesting that UBA1 directly has an important role in disease pathogenesis. Tetrahydroindoles that alter the processing of amyloid precursor protein were tested in these various models and revealed that three of these compounds rescued motor neuron defects in smn morpholino knockdown zebrafish ( Gassman et al, 2013 ). More generally, the results suggest that SMA could be an axonopathy (a disease in which the normal function of axons is disrupted), suggesting novel strategies for treating the disease.…”
Section: Spinal Muscular Atrophy (Sma)mentioning
confidence: 99%
“…238 Interestingly, pharmacological compounds known to rescue kinesin-mediated larval locomotion in Drosophila stimulated neurite growth in rat spinal neurons and rescued motor neuron development in a Zebra fish model of SMA. 239 Taken together, these observations suggest that SMN has a role in axonal transport and may form the unique cargo complex that interacts with MT motors.…”
Section: Motor Proteins and Regulatory Modelsmentioning
confidence: 80%
“…A study by Gassman et al found that small molecules known for suppressing Kinesin in Drosophila (SBL-154, SBL-185, and SBL-190) can rescue motor axon abnormalities from transgenic Smn-deficient and MO-injected zebrafish SMA models. However, the authors did not find an increase in the lifespan of transgenic Smn-deficient zebrafish lines when embryos were treated with SBL-154, suggesting that the effect of this compound could be restricted to motor neurons [43].…”
Section: Transient Smn Antisense Morphantsmentioning
confidence: 94%